Evaluasi Kinerja Simpang Empat Bersinyal di Kota Malang - Andi Syaiful Amal; Chairil Saleh; Azhar Adi Darmawan (Universitas Batanghari Jambi, 2022)
An intersection is a part of a road where currents from various directions or directions meet. This is what causes conflicts between currents from opposite directions and intersect each other, resulting in congestion along the intersection arm. The signalized intersection on Jl. Panglima Sudirman – Jl. Urip Sumoharjo – Jl. Pattimura is one of the main network junctions in Malang City, precisely located in an area that provides several public facilities, namely the National Defense Field, Kota Baru Station and Klojen Market. This intersection connects to public places such as the city center, schools, offices and others. This reseach aims to evaluate the performance of the intersection and the degree of saturation as well as the level of service at the signalized intersection at the current condition based on the Indonesian Road Capacity Manual (MKJI) 1997. This reseach uses empirical methods to obtain data from observations that occur in the field. From the results of the reseach the degree of saturation (DS) on the north approach was 0.89, with queue length (QL) = 140.30 m, south approach 0.84, with queue length (QL) = 97.25 m, east approach 0, 49 with queue length (QL) = 69.25 m and the western approach 0.56 with queue length (QL) = 54.40 m. The average delay of the intersection is 27.31 sec/pcu and is included in the value of service level of service D.